ANALISIS KARAKTERISTIK STRUKTUR GEDUNG RUMAH SAKIT DENGAN DIBERI PERKUATAN DIAFRAGMA PELAT LANTAI PADA GEDUNG CIPUTRA HOSPITAL - Krisna Dwi Sanjaya; Sumaidi; Nia Dwi Puspitasari (Racic : Rab Construction Research, 2025)
The structural planning of the hospital is designed as an earthquake resistant building. The beam-column connection area is a vulnerable area that must be designed by taking into account the inelastic deformation in the event of an earthquake. Therefore, a floor slab diaphragm is used as an earthquake resisting system. In this study, the floor slab diaphragm is modelled as a rigid diaphragm and is expected to provide lateral resistance to a ductile structure. To determine the level of ductility of a structure, the pushover analysis method is used. Pushover analysis is an analysis to determine the level of collapse of a structure against an earthquake and can determine the level of ductility of a structure. From the analysis results, the ductility value for the x direction is 1.55 and for the y direction is 2.15. So, the behaviour of the building structure after being reinforced with a floor plate diaphragm has a partial ductility level with a structural performance level of Immediate Occupancy (IO), which means a condition where the structure is still safe and strong to use activities shortly after an earthquake occurs.